Malignant perivascular epithelioid cell tumor of the uterus with aggressive behaviour: A case report - Prodanova, Irina; Kubelka-Sabit, Katerina; Basheska, Neli (Blackwell Publishing Ltd., 2008)
Background. The perivascular epithelioid cell tumor (PEComa) is recognized by the World Health Organization as a mesenchymal neoplasm showing at least partial morphological and immunohistochemical evidence of a putative perivascular epithelioid cell differentiation. This family of tumors includes angiomyolipoma (AML), lymphangioleiomyomatosis (LAM), clear cell sugar tumor of the lung and distinctive clear cell tumors at various other anatomic sites. Occasionally, PEComas are associated with the tuberous sclerosis complex (TSC). Because non-AML/non-LAM PEComas are extremely rare and their nature and prognostic factors undefined, we present a case of uterine PEComa with obviously aggressive behavior. Case report. A 55-year-old (gravida-2, para-2) presented with a large uterine mass palpated during a routine gynaecological examination. The patient did not have any stigmata or family history of TSC, and had no history of melanoma. A transvaginal ultrasound revealed an enlarged uterus with a heterogeneous mass which size was estimated at 9 x 9 cm. The clinical impression of the lesion was a leiomyoma. Total abdominal hysterectomy with bilateral salpingo-oophorectomy and omentectomy was performed 9 months later, and the pathohistological diagnosis was malignant PEComa of the uterus with metastases in the omentum. Three months after the surgical intervention the patient is still receiving adjuvant chemotherapy and there is no evidence of recurrence. Results. The uterine body was enlarged and measured 12 x 14 x 8 cm, with lobulated surface. Within the myometrium there was a poorly demarked gray-ten nodular tumor occupying the fundus, anterior and posterior walls with focally hemorrhagic areas and necrosis on cut surface. The largest diameter of the tumor was 14 cm. In the adipose tissue of the omentum there were numerous nodular tumor masses whose diameters ranged from 1 to 3 cm. Histologically, the tumor demonstrated a tongue-like growth pattern and was composed of large epithelioid cells with clear or eosinophilic cytoplasm, partially arranged around blood vessels The nuclei were mainly round, centrally located, and vesicular, with moderate to severe pleomorphism and hyperchromatism. Extensive cellular atypia, including bizarre multinucleated giant cells with large nuclei and nucleoli, was present as well. Mitotic count was high (15 per 50 HPFs), with prominent coagulative tumor necrosis. The microscopic examination of the nodular tumors from the omentum exhibited the same morphological features. Immunohistochemically, the tumor cells showed positivity for HMB-45 and smooth muscle actin while they were negative for cytokeratins, carcinoembryonic antigen, S-100 protein, CD-10, caldesmon and desmin. Immunoreactivity for vimentin was inconspicuous. The estrogen and progesterone receptors were also negative. A proliferative index of 30% was noted with Ki-67 immunostaining. The morphology and immunohistochemical profile of the lesions was consistent with PEComa. Conclusion. Due to the fact that a vast majority of PEComas has a benign course of disease or is considered to be of uncertain malignant potential, we present this case with evident aggressive behaviour since we believe that the histological features of this tumor can serve as a model for defining of the criteria for potentially malignant PEComas.
Keywords: uterus; perivascular epithelioid cell tumor (PEComa); histopathology; immunohistochemistry; prognosis